Perencanaan Ulang Overpass Cabe Raya, Ciputat, Tangerang Selatan Berbasis BIM - Galang Huda Nugraha; Onyvia Whika Elfrida; Asri Nurdiana; Riza Susanti (Jurnal Sipil dan Arsitektur, 2025)
BIM (Building Information Modeling) includes various important information in design. Modeling with BIM technology used in infrastructure planning is a form of technological development that presents digital physical and functional planning objects. The Cabe Raya overpass was built with the aim of reducing the congestion that occurs on the Pondok Cabe Raya road, South Tangerang. This planning aims to re-plan the construction of the Cabe Raya overpass based on BIM by modeling 4D using the Tekla Structures application. This re-planning will carry out analysis of data obtained from the project site review. The loading method refers to the Bridge and Highway Loading Standards (SNI 1725 2016). This planning goes through the main stages, namely, analysis of loading data then planning manual structural calculations, planning the cost budget design using Ms. Projects. It is planned that from the results of the preparation of the budget plan that will be needed is Rp. 8,930,872,000.00 and is planned to be completed in approximately 8 months.